THE EQUIVALENCE OF TOEP FORMS - Madya, Suwarsih; Retnawati, Heri; Purnawan, Ari; Putro, Nur Hidayanto Pancoro Setyo; Apino, Ezi (TEFLIN Journal, 2019)
This explorative-descriptive study set out to examine the equivalence among Test of English Proficiency (TOEP) forms, developed by the Indonesian Testing Service Centre (ITSC) and co-founded by The Association for The Teaching of English as a Foreign Language in Indonesia (TEFLIN) and The Association of Psychology in Indonesia. Using a quantitative approach, the researchers collected the data through documenting the responses of those taking TOEP in 2016 and 2017, involving six TOEP forms in 2016 and four TOEP forms in 2017. All the forms were developed using the same test grid and construct to measure the listening and reading skills. The equality among the six forms was tested using the equating technique, which involved (1) the estimation of the item parameter using the Rasch model, (2) examination of the test characteristics curve for each form, and (3) interpretation of results. The results showed that all the TOEP forms used in 2016 and 2017 were equal with one another. It can be concluded then that the developed TOEP forms have the same level of difficulty and ensure justice for all test takers.